Incorporation of a recirculating mobile lipid pool description into the cyclic volatile siloxane (cVMS) PBPK model captures terminal clearance of D4 after repeated inhalation exposure in F344 and SD Rats. (15th February 2023) - Campbell, Jerry; Andersen, Melvin; Gentry, Robinan; Landingham, Cynthia Van; Clewell, Harvey
Abstract: The most recent version of the octamethylcyclotetrasiloxane (D4 ) physiologically based pharmacokinetic (model) was developed using the available kinetic studies in male and female F344 rats. Additional data, which had not been included in the D4 model development, allowed for a more detailed assessment of the loss of D4 following long-term exposure in both SD and F344 rats. This new data demonstrated a deficiency in the published PBPK model predictions of terminal concentrations of D4 in plasma and fat 14 days after the end of exposures for 28-days, 6 h/day, where the model predictions were an order of magnitude lower than the data. To capture this time-point without altering the end-of-exposure peak concentrations in blood and fat required conversion of the one-way (liver to fat) mobile lipoprotein pool (MLP) into a bi-directional pool between liver and fat. Simulation of the D4 pharmacokinetics in the SD rat, as opposed to the F344 rat, also required a reduction of both fold induction of liver metabolism (KMAX: 5- to 2-fold) and maximal rate of metabolism (VMAXC: 5.0–1.54 mg/kg 0.75 ). The revised MLP description was extended to the human D4 model using a parallelogram approach between rat and human MLP parameters to establish the parameters for the current model in the absence of similar long-term clearance data in the human. The revised human D4 model provided good fits to the human inhalation and dermal exposure studies while not appreciably altering cross-species dose metrics based on the free concentration of D4 in blood. Highlights: Incorporation of a recirculating lipid associated pool of D4 into the D4 PBPK model captured the clearance of D4 in F344 and SD rats. Refined the D4 model to more accurately reflect metabolism in the SD rat liver. Assessed impact of the hepatic metabolic differences in SD and F344 male and female rats on D4 clearance in the cVMS model. The refined D4 model accurately predicts human plasma and exhaled air concentrations following inhalation or dermal exposure. cVMS PBPK model was converted from legacy software (acslX) to run in R using openly available packages.